Peripartum Cardiomyopathy Presenting with Predominant Left Ventricular Diastolic Dysfunction: Efficacy of Bromocriptine - Piercarlo Ballo; Irene Betti; Giuseppe Mangialavori; Leandro Chiodi; Gherardo Rapisardi; Alfredo Zuppiroli (Case Reports in Medicine)
Management of patients with peripartum cardiomyopathy (PPCM) is still a major clinical problem, as only half of them or slightly more show complete recovery of left ventricular (LV) function despite conventional evidence-based treatment for heart failure. Recent observations suggested that bromocriptine might favor recovery of LV systolic function in patients with PPCM. However, no evidence exists regarding its effect on LV diastolic dysfunction, which is commonly observed in these patients. Tissue Doppler (TD) is an echocardiographic technique that provides unique information on LV diastolic performance. We report the case of a 37-year-old white woman with heart failure (NYHA class II), moderate LV systolic dysfunction (ejection fraction 35%), and severe LV diastolic dysfunction secondary to PPCM, who showed no improvement after 2 weeks of treatment with ramipril, bisoprolol, and furosemide. At 6-week followup after addition of bromocriptine, despite persistence of LV systolic dysfunction, normalization of LV diastolic function was shown by TD, together with improvement in functional status (NYHA I). At 18-month followup, the improvement in LV diastolic function was maintained, and normalization of systolic function was observed. This paper might support the clinical utility of bromocriptine in patients with PPCM by suggesting a potential benefit on LV diastolic dysfunction.